PENGARUH UKURAN PERUSAHAAN, STRUKTUR MODAL, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN YANG TERCATAT PADA INDEKS LQ45 BURSA EFEK INDONESIA TAHUN 2015-2019 - Putu Nanda Diantari; Ni Nyoman Sri Rahayu Trisna Dewi; Ni Made Ernila Junipisa (Universitas Triatma Mulya, 2021)
The purpose of this research is to determine the effect of company size, capital structure and dividend policy on company value listed on the LQ45 index of the Indonesia Stock Exchange in 2015-2019. The population of this research is 68 companies listed on the LQ45 index in 2015 - 2019. The sample consisted of 25 companies, with a total of 125 observations. The sampling technique used purposive sampling method with certain criteria. The data analysis technique used in this research is multiple linear regression test. The results of this research indicate that company size has a positive and significant effect on the value of companies listed on the LQ45 index of the Indonesia Stock Exchange in 2015-2019, capital structure has a positive and significant effect on the value of companies listed on the LQ45 index of the Indonesia Stock Exchange in 2015-2019, and dividend policy has a positive and significant effect on company value listed on the LQ45 index of the Indonesia Stock Exchange in 2015-2019.